Rethinking Production under Uncertainty - Cochrane, John H (The Review of Asset Pricing Studies, 2021)
Conventional models of production under uncertainty specify that output is produced in fixed proportions across states of nature. I investigate a representation of technology that allows firms to transform output from one state to another. I allow the firm to choose the distribution of its random productivity from a convex set of such distributions described by a limit on a moment of productivity scaled by a natural productivity shock. The model produces a simple discount factor that is linked to productivity and that can be used to price a wide variety of assets, without regard to preferences. Received November 26, 2019; editorial decision May 23, 2020 by Editor Jeffrey Pontiff. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.